BRANDING ADMINISTRASI PUBLIK: STRATEGI MEMBANGUN CITRA DAN KEPERCAYAAN MASYARAKAT TERHADAP LAYANAN PEMERINTAH - Jackson Yumame (CV. Adiba Aisha Amira, 2026)
Public administration branding is a crucial strategy in the digital age for building a positive image and public trust in government services. This article aims to outline the concept of branding in public administration and effective strategies for building public image and trust. The research employs a literature review method with a descriptive-analytical approach. The findings indicate that branding in the public sector differs from that in the private sector as it focuses on flagship products within service delivery, rather than merely visual identity. The eight main dimensions of public branding encompass behavioural, managerial, physical, relational, sociocultural, representational, financial, and political dimensions that shape an institution’s brand equity. Effective strategies include strengthening service quality based on standards, digital branding through e-government and social media, responsive public communication, enhancing transparency and accountability, and public participation in service evaluation. Well-managed branding can create a positive image, strengthen public trust, and increase public participation in supporting government programmes. The implementation of an integrated branding strategy is necessary for government agencies to build strong relationships with the public and enhance their legitimacy in carrying out governmental functions.